4CPS-274 To identify the proportion of emergency department patients that advanced clinical practice-trained pharmacists can actually manage. (March 2019) - Terry, D; Huynh, C; Aiello, M; Whyte, SA; Hughes, E
Abstract : Background: Ongoing shortages of medical staff requires action to maintain clinical services to UK emergency departments (ED). The large Pharmacists In Emergency Departments (PIED) study demonstrated the potential for Advanced Clinical Practice (ACP)-trained pharmacist clinicians to manage patients attending EDs. 1 ACP training is now offered by UK universities against a national framework.2 ACP postgraduate training enables pharmacists to become independent prescribers and to learn diagnostic and clinical examination skills. This present study demonstrates the actual utility of ACP pharmacist clinicians to manage ED attendees, as part of a multi-professional clinical team. Pharmacists may have the capacity and capability to support activity in EDs. Purpose: To identify the proportion of ED patients that ACP-trained pharmacists can actually manage, to support national funding of postgraduate training. Material and methods: Recorded details of 1998 ED patient attendee cases, obtained from PIED data, were considered by ACP pharmacists using a bespoke database (Microsoft Excel 2013). Approximately 400 cases were categorised by each of five ACP pharmacists working in EDs in England. The cases represented a broad cross-section of ED attendees. No attempt was made to select patients with simplified presentations. Case details included: patient age, gender, presenting complaint, clinical specialty and long-term medication. ACP pharmacists categorised patients according to whether they could manage the patient: given their current (ACP) training; or with further training; or if the patient was beyond their clinical competence and required management by a doctor. It was assumed that the ACP pharmacist would be working within a suitably equipped ED as part of a multidisciplinary clinical team. Results: Fifty-nine per cent of ED attendees (n=1179/1998) can be managed by ACP pharmacists. This exceeds the PIED study prediction of 36%. Participants indicated that a further 15.2% (n=304/1998) could be managed by ACP pharmacists after further training. Conclusion: ACP pharmacists can clinically manage 59% of patients attending EDs as part of the multidisciplinary workforce, potentially increasing to 74% patients with further training. References and/or acknowledgements: 1. Hughes E, et al. Future enhanced clinical role of pharmacists in emergency departments in England: multi-site observational evaluation. Int J Clin Pharm 2017;39:960–8. 2. NHS/HEE. Multi-professional framework for advanced clinical practice in England. HEE/NHS; 2017. No conflict of interest.